The implication of humor discourse in the Tonight Show television program - Dita Intan Pramukti; Asep Purwo Yudi Utomo (Universitas Negeri Yogyakarta, 2020)
Humor discourse is a form of language that deviates from the rules of speech and conversation principles. Humor is a form of contradiction or deviation from the constraints of language. One of the humor discourse that presents language use conditions with a particular speech strategy is NET TV Tonight Show. This television program may contain speech offenses at the event. This study aims to describe and explain the implicature of humor discourse in the Tonight Show. In this study, researchers used a qualitative approach with the content analysis method and the pragmatic theory approach. The data is in the form of humor discourse in the Tonight Show television program, which is aired on NET TV. Still, researchers take the data from the Tonight Show uploaded on YouTube, collected by recording and recorded techniques. The data is analyzed by using an interactive model. The results showed that the implicature of humor discourse in the Tonight Show was in the form of mentioning, insinuating, revealing, protesting, informing, rejecting, accusing, asking, and saying. The benefit of this study is to know the humor discourse contained in the Tonight Show.